Analisis Prestasi Belajar Matematika : Dampak Model Pembelajaran Kooperatif Tipe Think-Pair-Square Ditinjau dari Aktivitas Belajar - Suriati, Suriati (Desimal: Jurnal Matematika, 2019)
This study aims to describe the effectiveness of TPS (Think-Pair-Square) in terms of mathematical learning activities and the effectiveness of TPS in terms of learning achievement in mathematics. The method in this study was quasi-experimental. The study population was class IX students of SMP Negeri 24 Bandar Lampung Academic Year 2017/2018. The sample was obtained by random class technique and selected class IX D as the control class and class IX E as the experimental class. The research instrument used was a test of student achievement in the form of pre-test and post-test, learning activity questionnaire and observation sheet of learning activities of students. The results showed that the TPS learning model was effective in terms of the learning activities of students with a tcount = 6.604> t table = 2.05553 so that H0 was rejected. In addition, TPS was also effective in terms of the learning achievement of the analysis results. It was found that the p value was 0,000 <α so that H0 was rejected, meaning there were differences in the results of the pre-test and post-test. This means that the Think Pair Square (TPS) learning model is effective in terms of learning achievement.